Peran Notaris dalam Mencegah Keterlambatan Notifikasi Perseroan kepada Komisi Pengawas Persaingan Usaha - Siti Anisah; Muhammad Zaky Ridho Subakti (Jurnal Persaingan Usaha, 2022)
Notaries play a very significant role in the company acquisition process, including preventing delays in notification of acquisitions to the Indonesian Competition Commission (KPPU). This issue is related to the substance of Article 128 of Law Number 40 of 2007 concerning Limited Liability Companies and Article 1 of Law Number 2 of 2014 concerning Notary Positions. This research is a normative research supported by primary secondary and tertiary legal materials. The results show that notification of company acquisition is to prevent monopolistic practices and/or unfair competition. Such notification can be made starting from the acquisition plan by voluntarily conducting “consultation” until the mandatory notification time, which is 30 (thirty) days after the acquisition becomes legally effective. The Notary as a public official has the authority to make an authentic deed related to the acquisition, so that before ratifying the deed, the Notary can suggest to the company to conduct "consultation" first with KPPU.